1999
DOI: 10.1038/6326
|View full text |Cite|
|
Sign up to set email alerts
|

Acetylcholine receptor M3 domain: stereochemical and volume contributions to channel gating

Abstract: By defining the functional defect in a congenital myasthenic syndrome (CMS), we show that the third transmembrane domain (M3) of the muscle acetylcholine receptor governs the speed and efficiency of gating of its channel. The clinical phenotype of this CMS results from the mutation V285I in M3 of the alpha subunit, which attenuates endplate currents, accelerates their decay and causes abnormally brief acetylcholine-induced single-channel currents. Kinetic analysis of engineered alpha V285I receptors demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
75
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 29 publications
(19 reference statements)
8
75
0
3
Order By: Relevance
“…Any of these changes may reduce the energy barrier for channel opening and, thus, facilitate the transition from a closed to an open state. Mutations at Val-385 of the ␣ subunit of muscle type nACh receptors revealed that both volume and stereochemistry contribute to channel gating but not to binding affinity (39). The observation that some 5-HT 3A receptor mutants, such as R222F and R222I, exhibits spontaneous channel opening (14) is consistent with the notion that Arg-222 mutations can reduce the energy barrier for channel opening.…”
Section: Discussionsupporting
confidence: 72%
“…Any of these changes may reduce the energy barrier for channel opening and, thus, facilitate the transition from a closed to an open state. Mutations at Val-385 of the ␣ subunit of muscle type nACh receptors revealed that both volume and stereochemistry contribute to channel gating but not to binding affinity (39). The observation that some 5-HT 3A receptor mutants, such as R222F and R222I, exhibits spontaneous channel opening (14) is consistent with the notion that Arg-222 mutations can reduce the energy barrier for channel opening.…”
Section: Discussionsupporting
confidence: 72%
“…Also, the non-functionality of two of these mutations (␣M282W and ␣V285W) agree with the previous ␣M3 Torpedo study (32), thus suggesting that ␣Met-282 and ␣Val-285 are critical constraint positions in both AChR species. Furthermore, previous mutations at the ␣Val-285 position revealed that changes in stereochemistry and volume at this site affect the ion channel function of the AChR (23,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…MFVAI (blue font) and MLFTMIF*V*IS*S*II (highlighted in turquoise) were studied using tryptophan-scanning mutagenesis and patch clamp (32). V (violet font and italic) and F (blue font and italic) were studied using site-directed mutagenesis and patch clamp (23,31). F and S were labeled as lipid-exposed using photolabeling affinity (10).…”
mentioning
confidence: 99%
“…Electrophysiological studies were performed in BOSC cells (20) using the cell-attached patch-clamp method essentially as described previously (21). For electrophysiological studies, BOSC cells (20), a variant of the HEK293 cell line, were transfected with human wild-type or mutant nAChR subunit cDNAs using calcium phosphate precipitation.…”
Section: Methodsmentioning
confidence: 99%